(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article explores theoretical, methodological and practical aspects of implementing the "language portfolio" technology in teaching Russian as a foreign language. Special attention is paid to the analysis of academic sources, research methods used, and practical applications in both classroom and online instruction. The article outlines challenges and provides practical recommendations for the effective integration of the portfolio into the educational process.